SKEPTICISM, MESSAGE ENGAGEMENT AND PURCHASE INTENTIONS: THE ROLE OF CONSTRUAL LEVEL IN BRAND CAMPAIGNS DURING GLOBAL HUMANITARIAN CRISES - Shafa Una Putri Purnomo; Dian Purworini (Perspektif Komunikasi Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2025)
This study explores how consumer skepticism and message engagement influence purchase intention in cause-related marketing (CRM) campaigns through the framework of Construal Level Theory (CLT). Focusing on Almaz Fried Chicken campaigns that emerged during global humanitarian crises, the research examines consumer responses toward its humanitarian themed campaigns. Using a quantitative explanatory method, 100 data were collected from respondents in Surakarta who were familiar with the brand’s campaign. Multiple linear regression analysis was employed to test the effects of skepticism (X₁) and message engagement (X₂) on purchase intention (Y) of Almaz Fried Chicken campaigns. The results show that both skepticism and message engagement significantly and positively affect purchase intention, with skepticism (β = 0.408, p < 0.001) having a stronger impact than message engagement (β = 0.271, p < 0.001). Together, these variables explain 80.01% of the variance in purchase intention. The findings indicate that higher levels of skepticism and engagement reflecting abstract construal thinking lead to more favorable consumer evaluations of CRM messages. Research contributes to the understanding of how psychological distance and moral perception shape consumer responses to Almaz Fried Chicken social campaigns.